Digital Transformation of Women-Owned MSMEs: Marketing Strategies to Adapt to The Dynamics of Consumer Behavior in The Digital Era - Octafia, Srimona; Malik, Rio Andika; Widia, Elsa (Universitas Bina Sarana Informatika, 2025)
Women-owned MSMEs play a strategic role in the national economy. However, many women MSMEs do not yet have adequate digital capacity to respond to changes in consumer behavior that now rely on technology in making purchasing decisions. In addition, structural barriers such as limited access to technology and capital, as well as socio-cultural barriers such as gender stereotypes and double workloads, complicate the process of adopting digitalization. Although many studies discuss these challenges, there are still limited studies that specifically explore the digital marketing strategies implemented by women-owned MSMEs in response to the dynamics of consumer behavior, especially in the local context. This study aims to analyze the digital marketing strategies adopted by women-owned MSMEs in Padang City. The approach used is a mixed method with an explanatory sequential design, starting with a survey of 125 women MSMEs, followed by in-depth interviews. The findings of this study indicate a significant shift in consumer behavior in the digital era, emphasizing the importance of convenience and ease in purchasing decisions. Therefore, it is crucial for women-led MSMEs to understand these behavioral changes and master appropriate marketing strategies to thrive in this evolving market landscape.